Purchase Intention of Batam People Against Foreign Sellers in the Marketplace - Erilia Kesumahati; Jecki (Universitas Trisakti, 2022)
This research is motivated by increased product purchases from overseas sellers in Batam City. This increase in sales indicates an increase in purchase intention on overseas seller marketplace products. This study aimed to analyze the effect of trust, perceived risk, price, perceived benefit, product quality, and E-WOM on purchase intention. This study uses quantitatives methods and data collected by questionnaire technique. Respondent's study included as many as 300 people living in Batam City on the condition that they have shopped at foreign sellers in marketplace. Six hypotheses were formulated and tested using T-test analysis. The results showed that perceived risk, perceived benefit, price, and E-WOM significant positively affected purchase intention. Meanwhile, trust and product quality had no significant positive effect on purchase intention. Therefore, Batam City MSMEs must be more innovative in making products and have a broader range of marketing methods to increase MSMEs of local products rather than imported goods from abroad.